Complications and Patient-reported Outcomes in Transfemale Vaginoplasty: An Updated Systematic Review and Meta-analysis. Issue 3 (19th March 2021) - Bustos, Samyd S.; Bustos, Valeria P.; Mascaro, Andres; Ciudad, Pedro; Forte, Antonio J.; Del Corral, Gabriel; Manrique, Oscar Javier
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Vaginoplasty aims to create a functional feminine vagina, sensate clitoris, and labia minora and majora with acceptable cosmesis. The upward trend in the number of transfemale vaginoplasties has impacted the number of published articles on this topic. Herein, we conducted an updated systematic review on complications and patient-reported outcomes. Methods: A update on our previous systematic review was conducted. Several databases including MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Scopus were assessed. Random effects meta-analysis and subgroup analyses were performed. Results: After compiling the results of the update with the previous systematic review, a total of 57 studies pooling 4680 cases were included in the systematic review, and 52 studies were used in the meta-analysis. Overall pooled data including any surgical technique showed rates of 1% [95% confidence interval (CI) <0.1%–2%] of fistula, 11% (95% CI 8%–14%) of stenosis and/or strictures, 4% (95% CI 1%–9%) of tissue necrosis, and 3% (95% CI 1%–4%) of prolapse. Overall satisfaction was 91% (81%–98%). Regret rate was 2% (95% CI <1%–3%). Average neovaginal depth was 9.4 cm (7.9–10.9 cm) for the penile skin inversion and 15.3 cm (13.8–16.7 cm) for the intestinal vaginoplasty. Conclusions: Transfemale vaginoplasty is a key component of the comprehensive surgical treatment of transfemale patients with gender dysphoria. Over time, we will see an increased demand for these procedures, so adequate surgical training, clinical/surgical experience, and research outcomes are required, as we continue to strive to provide the best care possible for a population in need.